2016
DOI: 10.21093/di.v16i1.155
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic Symbols through Audiolingual Method to Improve the Students’ Listening Skill

Abstract: Phonetic symbols present linguistics feature to how the words are pronounced or spelled and they offer a way to easily identify and recognize the words. Phonetic symbols were applied in this research to give the students clear input and a comprehension toward English words. Moreover, these phonetic symbols were applied within audio-lingual method which provided repetitions, memorizations, and drills through audio media. This research used Classroom Action Research (CAR) design. The objective of this research w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, when the students were presented some similar words sound, they could differentiate them appropriately. This case implied that having individual word practices was easy enough to accomplish but it was not in complex words or text ( (Samawiyah & Saifuddin, 2016). The observation found that the phonetic method was not completely done.…”
Section: Activity In Cycle Imentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the students were presented some similar words sound, they could differentiate them appropriately. This case implied that having individual word practices was easy enough to accomplish but it was not in complex words or text ( (Samawiyah & Saifuddin, 2016). The observation found that the phonetic method was not completely done.…”
Section: Activity In Cycle Imentioning
confidence: 99%
“…But, it cannot be satisfyingly stated that in the first cycle, there was no one student could enhance their pronunciation in a very good score because there was nothing media to support the phonetic method implemented. It means that the teacher relied on reading and phonetic symbols from his skills in pronouncing every single word in the texts (Samawiyah & Saifuddin, 2016).…”
Section: Fig 1 Flowchart Of Pronunciation Skills Through Phonetic Met...mentioning
confidence: 99%
“…For instance, in term of listening skill, El Meysarah (2015) found that listening ability of state university of Surabaya students is good enough, meanwhile in Riau university, listening ability of Riau university students is still low (Ristanti, et al, 2016). Some efforts have been implemented by the English teachers and lecturers to cope the problems of listening skill of the English learners (Afsharrad & Nafchi, 2015;Samawiyah & Saifuddin, 2016;Hanafi, 2016;Cendra, 2017) There have been numerous attempts to describe listening comprehension in terms of taxonomies of sub-skills. This approach is based on the notion that these skills underlie the process, and the act of listening consists of the application of various separate skills (Barta, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It had more focus on the function rather than the form, parting ways with the typical grammar based learning. It was not only helpful at language learning but in many cases it was helpful in almost perfect acquisition of the target accent as well; though a language can be learnt very well without acquiring the target accent (Samawiyah, & Saifuddin, 2016).…”
Section: Introductionmentioning
confidence: 99%